Uncritical Patriotism and Belief in COVID-19 Conspiracies - Rieger, Marc Oliver (Frontiers in Sociology, 2022)
The outbreak of the COVID-19 pandemic has also led to many conspiracy theories. While the origin of the pandemic in China led some, including former US president Donald Trump, to dub the pathogen "Chinese virus" and to support anti-Chinese conspiracy narratives, it caused Chinese state officials to openly support anti-US conspiracy theories about the "true" origin of the virus. In this article, we study whether nationalism, or more precisely uncritical patriotism, is related to belief in conspiracy theories among normal people. We hypothesize based on group identity theory and motivated reasoning that for the particular case of conspiracy theories related to the origin of COVID-19, such a relation should be stronger for Chinese than for Germans. To test this hypothesis, we use survey data from Germany and China, including data from the Chinese community in Germany. We also look at relations to other factors, in particular media consumption and xenophobia.